Mixed sandwich imido complexes of Uranium(V) and Uranium(IV): Synthesis, structure and redox behaviour - Tsoureas, Nikolaos; Cloke, F. Geoffrey N. (Journal of Organometallic Chemistry, 2018)
The mixed sandwich U(III) complex {U[η8-C8H6(1,4-Si(iPr)3)2](Cp*)(THF)} reacts with the organic azides RN3 (R = SiMe3, 1-Ad, BMes2) to afford the corresponding, structurally characterised U(V) imido complexes {U[η8-C8H6(1,4-Si(iPr)3)2](Cp*)(NR)}. In the case of R = SiMe3, the reducing power of the U(III) complex leads to reductive coupling as a parallel minor reaction pathway, forming R-R and the U(IV) azide-bridged complex{[U]}2(μ-N3)2, along with the expected [U] = NR complex. All three [U] = NR complexes show a quasi-reversible one electron reduction between −1.6 and −1.75 V, and for R = SiMe3, chemical reduction using K/Hg affords the anionic U(IV) complex K+{U[η8-C8H6(1,4-Si(iPr)3)2](Cp*) = NSiMe3}-. The molecular structure of the latter shows an extended structure in the solid state in which the K counter cations are successively sandwiched between the Cp* ligand of one [U] anion and the COTtips2 ligand of the next.
Keywords: Electrochemistry; Imido; Mixed-sandwich; Uranium